Pediatric Metastatic Pheochromocytoma and Paraganglioma: Clinical Presentation and Diagnosis, Genetics, and Therapeutic Approaches - Kuo, Mickey J. M.; Nazari, Matthew A.; Jha, Abhishek; Pacak, Karel (Frontiers in Endocrinology, 2022)
Although pediatric pheochromocytomas and paragangliomas (PPGLs) are rare, they have important differences compared to those in adults. Unfortunately, without timely diagnosis and management, these tumors have a potentially devastating impact on pediatric patients. Pediatric PPGLs are more often extra-adrenal, multifocal/metastatic, and recurrent, likely due to these tumors being more commonly due to a genetic predisposition than in adults. This genetic risk results in disease manifestations at an earlier age giving these tumors time to advance before detection. In spite of these problematic features, advances in the molecular and biochemical characterization of PPGLs have heralded an age of increasingly personalized medicine. An understanding of the genetic basis for an individual patient’s tumor provides insight into its natural history and can guide clinicians in management of this challenging disease. In pediatric PPGLs, mutations in genes related to pseudohypoxia are most commonly seen, including the von Hippel-Lindau gene (VHL) and succinate dehydrogenase subunit (SDHx) genes, with the highest risk for metastatic disease associated with variants in SDHB and SDHA. Such pathogenic variants are associated with a noradrenergic biochemical phenotype with resultant sustained catecholamine release and, therefore, persistent symptoms. This is in contrast to paroxysmal symptoms (e.g., episodic hypertension, palpitations, and diaphoresis/flushing) as seen in the adrenergic, or epinephrine-predominant, biochemical phenotype (due to episodic catecholamine release) that is commonly observed in adults. Additionally, PPGLs in children more often present with signs and symptoms of catecholamine excess. Therefore children, adolescents, and young adults present differently from older adults (e.g., the prototypical presentation of palpitations, perspiration, and pounding headaches in the setting of an isolated adrenal mass). These presentations are a direct result of genetic determinants and highlight the need for pediatricians to recognize these differences in order to expedite appropriate evaluations, including genetic testing. Identification and familiarity with causative genes inform surveillance and treatment strategies to improve outcomes in pediatric patients with PPGL.